Analysis of the Impact of Project-Based Learning Education Innovations on the Merdeka Belajar Program in Primary School X in Jakarta - Purwadianto, Purwadianto (Enigma in Education, 2023)
Project-based learning (PBL) is one of the educational innovations encouraged by the Merdeka Belajar program. PBL is a learning approach that actively involves students in solving complex problems or projects. PBL has the potential to improve the quality of learning, develop student skills, and develop student character. PBL takes longer to complete than traditional learning. This is because PBL involves students in a more complex process. PBL requires greater resources, such as equipment, materials, and time. This is because PBL involves students in a more complex process. Teachers who implement PBL must have higher skills in planning, implementing, and assessing projects. This is because PBL involves students in a more complex process. To overcome these challenges, proper planning and support are needed. Schools need to adapt the curriculum and provide the resources needed for PBL. Teachers need to receive training or support to develop the skills they need to implement PBL effectively.